YouNICon: YouTube’s CommuNIty of Conspiracy Videos - Yi Liaw, Shao; Huang, Fan; Benevenuto, Fabricio; Kwak, Haewoon; An, Jisun (Proceedings of the International AAAI Conference on Web and Social Media, 2023)
Conspiracy theories are widely propagated on social media. Among various social media services, YouTube is one of the most influential sources of news and entertainment. This paper seeks to develop a dataset, YOUNICON, to enable researchers to perform conspiracy theory detection as well as classification of videos with conspiracy theories into different topics. YOUNICON is a dataset with a large collection of videos from suspicious channels that were identified to contain conspiracy theories in a previous study. Overall, YOUNICON will enable researchers to study trends in conspiracy theories and understand how individuals can interact with the conspiracy theory producing community or channel. Our data is available at: https://doi.org/10.5281/zenodo.7466262.